Effect of Garlic Extract on Cholesterol and Glucose in High-Fat Diet STZ Induced Rats - Veronica Veronica; Ermi Girsang; Linda Chiuman; Sunny Puspita (Eduvest - Journal of Universal Studies, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by elevated blood glucose levels and is linked to an increased risk of hypercholesterolemia. Garlic (Allium sativum Linn), which contains bioactive compounds such as saponins and flavonoids, has potential for managing these conditions. This study aimed to evaluate the effects of garlic extract on two parameters: blood cholesterol levels in Wistar rats fed a high-fat diet and blood glucose levels in rats induced with streptozotocin (STZ). A laboratory experimental post-test-only control group design was used. For cholesterol assessment, hypercholesterolemic rats were treated with garlic extract at doses of 0.05, 0.10, or 0.20 g/head/day, alongside negative and positive control groups. For glucose assessment, STZ-induced diabetic rats received garlic extract at 100, 250, or 500 mg/kgBW/day, with corresponding control groups. Garlic extract significantly reduced mean cholesterol levels in a dose-dependent manner (130.60 mg/dL, 121.80 mg/dL, and 112.00 mg/dL for 0.05, 0.10, and 0.20 g/head/day, respectively). In contrast, mean blood glucose levels showed a marginal decrease with higher doses (282.80 mg/dL, 271.20 mg/dL, and 269.27 mg/dL for 100, 250, and 500 mg/kgBW/day), but no statistically significant differences were observed among groups (P = 0.706, one-way ANOVA). These findings suggest that garlic extract exhibits a significant cholesterol-lowering effect in hypercholesterolemic rats but does not markedly reduce blood glucose levels in STZ-induced diabetic rats at the tested dosages.